Rising temperatures, melting incomes: Country-specific macroeconomic effects of climate scenarios - Mohaddes, Kamiar; Raissi, Mehdi (PLOS Climate, 2025)
Quantifying the macroeconomic impact of climate change has been a focal point in academic and policy discussions since the early 1990s. The estimates of (global) GDP losses at future warming levels vary widely due to differing methodologies, complicating the formulation of effective climate policies. This study aims to bridge the gap between these varying estimates by quantifying country-specific annual per-capita GDP losses from global warming using the most recent climate scenarios of the Intergovernmental Panel on Climate Change (IPCC) under different mitigation, adaptation, and climate variability assumptions. Motivated by the need to inform policy decisions, we hypothesize that without substantial mitigation and adaptation efforts, global GDP per capita could decline by up to 24 percent under high-emissions climate scenarios by 2100. To test this hypothesis, we conduct a series of counterfactual exercises, investigating the cumulative income effects of annual temperature increases by the end of the century. Our findings reveal significant disparities in income losses across the 174 countries in our sample, highlighting that the impacts of climate change are not uniform but depend on the projected paths of temperatures and their variability.